Strategi Dakwah Bil Hikmah Media Sosial Facebook Terhadap Akun @pecintaudud (Ustadz Maududi) - Anida; Samsu; Neneng Hasanah; Zulqarnin; Jamaluddin; Muhsin Ruslan (Journal of Religion and Film, 2024)
Da'wah, or spreading Islamic teachings, is an obligation for Muslims to guide them towards the right path. In the contemporary era, the integration of technology, especially social media platforms such as Facebook, plays an important role in conveying religious messages. This research explores the strategic approach to Bil Hikmah da'wah implemented by the Facebook account @pecintaudud, associated with Ustadz Maududi. This research aims to understand how these accounts use sentimental, rational and sensory strategies to convey Islamic messages effectively. Despite being faced with challenges such as negative perceptions and limited resources, @pecintaudud shows resilience and commitment in spreading positive messages through creative content. This study emphasizes the significance of social media in contemporary da'wah, while highlighting the role of dedication and integration of technology in overcoming various challenges. This research uses descriptive qualitative research methods. Which, to obtain data for this thesis using interview techniques, observation and documentation. Furthermore, so that this research can be focused, the theory that is used as a reference in this thesis is dakwah strategy theory. Keywords: da'wah, bil hikmah, social media, facebook, ustadz maududi